IDENTIFICATION AND PHYLOGENETIC ANALYSIS OF IPOMOEA SPECIES COLLECTED FROM EASTERN INDIA USING INTER SIMPLE SEQUENCE REPEAT MARKERS - GYANA RANJAN ROUT; SUNIL KUMAR SENAPATI; SUBHASHREE APARAJITA (International Journal of Pharma and Bio Sciences, 2010)
Ipomoea genus is widely distributed in the tropical and subtropical regions of the world. The exploration of genetic diversity is pre-requisite for genome organization in the wild species and the related domesticated ones. Inter-simple Sequence Repeat (ISSR) markers was used to assess the identification of 21 important Ipomoea species and determination of the genetic relationships among these species. Out of 20 ISSR primers tested, twelve primers produced 218 detectable fragments, of which 207 (94.9 %) were polymorphic across the species. Each of the twelve primers produced fingerprint profile unique to each of the species studied, and thus could be solely used for their identification. Forty four unique bands specific to fifteen species were detected. These may be converted into species-specific probes for identification purposes. Genetic relationships among these species were evaluated by generating a similarity matrix based on the Dice coefficient and the Unweighted Pair Group Method with Arithmetic Average (UPGMA) dendogram. The results showed a clear cut separation of the 21 Ipomoea species and were in broad agreement with the morphology. Both molecular and morphological markers will be useful for preservation of the Ipomoea germplasm collected from Eastern part of India.